1996
DOI: 10.1007/bf00055320
|View full text |Cite
|
Sign up to set email alerts
|

The 93D (hsr-omega) locus of Drosophila: non-coding gene with house-keeping functions

Abstract: The 93D, or hsr-omega (heat-shock RNA-omega), locus of Drosophila melanogaster and other species of Drosophila, besides being induced as a member of the heat shock gene family, is also selectively and singularly inducible by a variety of agents, notably benzamide, colchicine and vitamin B6 (in species other than D. melanogaster). The genomic structure of this locus is highly conserved in all species, although the primary base sequence has diverged rapidly between species. Three transcripts (two nuclear and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 61 publications
0
21
0
2
Order By: Relevance
“…We showed (figure 1) that following ubiquitous expression of the hsrω-RNAi transgene or the EP alleles under the Act5C-GAL4 driver, the endogenous levels of the hsrω transcripts are depleted or enhanced, respectively, as expected. Since the hsrω-n transcript is exclusively nuclear Lakhotia and Sharma 1996) and this was effectively down-regulated by expression of the hsrω-RNAi transgene (present data and also see Lakhotia 2009a, b, 2010), it appears that, as in human cells (Robb et al 2005), nuclear RNA-induced silencing complexes (RISC) are present in Drosophila cells as well and can efficiently knock down the target nuclear RNA. Indirect evidence for the presence of nuclear RNAi machinery in Drosophila is also provided by the fact that localization of HP1 and heterochromatin formation (Pal-Bhadra et al 2004) and contacts between targets of Polycomb group (PcG) proteins (Grimaud et al 2006) are mediated by the RNAi machinery.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We showed (figure 1) that following ubiquitous expression of the hsrω-RNAi transgene or the EP alleles under the Act5C-GAL4 driver, the endogenous levels of the hsrω transcripts are depleted or enhanced, respectively, as expected. Since the hsrω-n transcript is exclusively nuclear Lakhotia and Sharma 1996) and this was effectively down-regulated by expression of the hsrω-RNAi transgene (present data and also see Lakhotia 2009a, b, 2010), it appears that, as in human cells (Robb et al 2005), nuclear RNA-induced silencing complexes (RISC) are present in Drosophila cells as well and can efficiently knock down the target nuclear RNA. Indirect evidence for the presence of nuclear RNAi machinery in Drosophila is also provided by the fact that localization of HP1 and heterochromatin formation (Pal-Bhadra et al 2004) and contacts between targets of Polycomb group (PcG) proteins (Grimaud et al 2006) are mediated by the RNAi machinery.…”
Section: Discussionmentioning
confidence: 69%
“…The 93D gene, so named because of its location at the 93D4 band on the right arm of chromosome 3 (www.flybase.org) is also designated as heat shock RNA omega or hsrω ) since it produces multiple heat-inducible transcripts with no identifiable protein product (Lakhotia and Mukherjee 1982;Hovemann et al 1986;Fini et al 1989). The near ubiquitous presence of hsrω transcripts in Drosophila cells (Bendena et al 1991;Mutsuddi and Lakhotia 1995;Lakhotia et al 2001) and the high degree of embryonic lethality associated with hsrω nullisomics (Mohler and Pardue 1984;Lakhotia and Ray 1996) suggest an essential requirement for this gene in vital housekeeping functions during normal development and differentiation of the fly (reviewed in Lakhotia and Sharma 1996;Lakhotia 2003). Since this gene forms one of the largest and transcriptionally most active puffs after a temperature shock (Mukherjee and Lakhotia 1979) and is uniquely inducible by a variety of amides (Lakhotia andMukherjee 1980, 1984;Tapadia and Lakhotia 1997), these transcripts seem to have a role in management of cellular stress as well (Lakhotia 2003;Jolly and Lakhotia 2006;Lakhotia et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The exact role of the hsr locus in development and under heat shock conditions is still unknown. It was reported that the 93D locus affected synthesis and/or turnover of Hsp70 [102]; furthermore, it was suggested that the role of the cytoplasmic transcript was to monitor the transcriptional machinery, while the nuclear trnscripts may be involved in synthesis and turnover/ transport of other transcripts [90]. These potential roles must be crucial, because even though this locus is dispensable for Hsps induction, it is necessary for fly survival after heat shock [92].…”
Section: Reviewsmentioning
confidence: 99%
“…A series of earlier studies from our laboratory had clearly shown that a variety of conditions can affect heat shock inducibility of the 93D puff without affecting its benzamide or colchicine inducibility, suggesting that heat shock and amides exert their effects on this locus through different pathways (reviewed in Lakhotia 1989;Lakhotia and Sharma 1996). Using promoter-lacZ reporter gene fusion constructs for germline transformation, it was further confirmed (Mutsuddi and Lakhotia 1995;Lakhotia and Mutsuddi 1996) that the upstream regulatory elements for heat shock and amide inducibility were distinct since only the developmental and heat shock regulatory elements of the hsrw gene were localized within the 840 bp upstream region; the response to amides was not elicited by this upstream region.…”
Section: Introductionmentioning
confidence: 98%
“…The hsr-omega (hsrw) locus at the 93D cytogenetic region of Drosophila melanogaster is a non-protein-coding gene that is developmentally expressed in almost all stages and cell types (Mutsuddi and Lakhotia 1995), is a member of the heat shock gene family and is also singularly induced, independent of the other heat shock or other genes, by amides such as benzamide, 3-amino-benzamide, colchicine, formamide, acetamide, or nicotinamide (Lakhotia and Sharma 1996;Tapadia and Lakhotia 1997). A series of earlier studies from our laboratory had clearly shown that a variety of conditions can affect heat shock inducibility of the 93D puff without affecting its benzamide or colchicine inducibility, suggesting that heat shock and amides exert their effects on this locus through different pathways (reviewed in Lakhotia 1989;Lakhotia and Sharma 1996).…”
Section: Introductionmentioning
confidence: 99%